2013
DOI: 10.1681/asn.2013010026
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Lupus Nephritis

Abstract: Lupus nephritis is an immune complex GN that develops as a frequent complication of SLE. The pathogenesis of lupus nephritis involves a variety of pathogenic mechanisms. The extrarenal etiology of systemic lupus is based on multiple combinations of genetic variants that compromise those mechanisms normally assuring immune tolerance to nuclear autoantigens. This loss of tolerance becomes clinically detectable by the presence of antinuclear antibodies. In addition, nucleic acids released from netting or apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
310
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(331 citation statements)
references
References 108 publications
6
310
0
15
Order By: Relevance
“…Overall, 34% of the patients in this study were found to have AKI, and among them only a small proportion showed mild microscopic hematuria. This finding is distinctly different from AKI occurring in the proliferative LN, which is usually accompanied by massive hematuria and hypertension (1,2). Nevertheless, renal biopsy is still crucially important to differentiate the diagnosis of AKI in SLE patients, as it is essential for deciding the treatment regimen.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, 34% of the patients in this study were found to have AKI, and among them only a small proportion showed mild microscopic hematuria. This finding is distinctly different from AKI occurring in the proliferative LN, which is usually accompanied by massive hematuria and hypertension (1,2). Nevertheless, renal biopsy is still crucially important to differentiate the diagnosis of AKI in SLE patients, as it is essential for deciding the treatment regimen.…”
Section: Discussionmentioning
confidence: 96%
“…Seventeen (34%) cases presented with AKI. Forty-seven (94%) patients achieved remission after immunosuppressive therapy for a median time of 4 weeks (IQR,2,8). Compared with the patients with minimal change and mesangial proliferation, patients with FSGS showed significantly higher incidence of AKI and severe tubule-interstitial injury and a much lower complete remission rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation is highly variable, the disease follows a relapsing and remitting course, and although standardized treatment has improved the short-and medium-term outlook, long-term prognosis remains poor in children with lupus with major organ involvement (1). Lupus has a higher incidence of renal involvement in children than in adults (2)(3)(4). Lupus nephritis is seen in nearly 50% patients with pediatric-onset SLE (pSLE), which may manifest as asymptomatic urinary findings, acute kidney injury, and even chronic renal disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…9 Interestingly, the corresponding autoantigens are exactly those that we identified as ligands for FH on the apoptotic cell surface, suggesting a possibility of disturbance of FH function in SLE. Glomerulonephritis is one typical manifestation of human SLE 10 and mutations in FH and another complement inhibitor CD46 are associated with earlier onset of nephritis in SLE patients. 11 FH-deficient (CFH − / − ) mice spontaneously develop membranoproliferative glomerulonephritis, which is dependent on C3 activation.…”
mentioning
confidence: 99%